A Purified Anthraquinone-Glycoside Preparation From Rhubarb Ameliorates Type 2 Diabetes Mellitus by Modulating the Gut Microbiota and Reducing Inflammation - Cui, Hong-Xin; Zhang, Ling-Shuai; Luo, Yang; Yuan, Ke; Huang, Zhi-Yong; Guo, Ying (Frontiers in Microbiology, 2019)
Rheum palmatum L. is widely used in traditional Chinese medicine for the treatment of constipation. Here, the therapeutic effects and underlying mechanisms of purified anthraquinone-glycoside preparation from rhubarb (RAGP) on the type 2 diabetes mellitus (T2DM) rats were investigated. After 6 weeks of metformin and RAGP treatment, the weight returned to normal. Fasting blood glucose (FBG), glycated serum protein (GSP), insulin concentration and HOMA-IR index had significantly decreased, and glucagon-like peptide-1 (GLP-1) concentrations had increased. Histological abnormalities in the pancreas and ileum had improved. These effects were associated with enhanced intestinal integrity, thereby reducing the absorption of lipopolysaccharide (LPS) and inflammation. To investigate whether RAGP ameliorated insulin resistance via effects on the gut microbiota, we performed 16s rDNA sequencing of ileal gut contents. This showed an amelioration of gut dysbiosis, with greater abundance of probiotic Lactobacillus and short-chain fatty acid-producing bacteria, and lower abundance of the Lachnospiraceae NK4A136 group and LPS-producing Desulfovibrio. The mechanism of the hypoglycemic effect of RAGP involves regulation of the gut microbiota, activation of the GLP-1/cAMP pathway to ameliorate insulin resistance. Thus, this study provides a theoretical basis for the use of RAGP to treat T2DM, and it may be a novel approach to restore the gut microbiota.